1991
DOI: 10.1063/1.461016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of experimental and theoretical integral cross sections for D+H2(v=1, j=1)→HD(v′=1, j′)+H

Abstract: We have measured the nascent HD(v′=1, j′) product rotational distribution from the reaction D+H2(v, j) in which the H2 reagent was either thermal (v=0, j) or prepared in the level (v=1, j=1) by stimulated Raman pumping. Translationally hot D atoms were obtained by uv laser photolysis of DBr or DI. Photolysis of DBr generated D atoms with center-of-mass collision energies (Erel) of 1.04 and 0.82 eV, which corresponded to the production of ground state Br and spin–orbit-excited Br*, respectively. The Erel values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 43 publications
3
57
0
2
Order By: Relevance
“…12,14 Accurate quantum mechanical reactive scattering calculations ͑on the ground electronic PES͒, with and without the GP effect included, have been carried out for the HϩH 2 system and its isotopic variants (DϩH 2 and HϩD 2 ) 14 -18 to obtain differential and integral cross sections. The cross sections obtained with the GP effect included were in much better agreement with the experimental results [19][20][21][22] than those obtained with the GP effect excluded. Hence, the GP effect is an important factor in accurate quantum scattering calculations done on the ground adiabatic electronic PES.…”
Section: Introductionsupporting
confidence: 75%
“…12,14 Accurate quantum mechanical reactive scattering calculations ͑on the ground electronic PES͒, with and without the GP effect included, have been carried out for the HϩH 2 system and its isotopic variants (DϩH 2 and HϩD 2 ) 14 -18 to obtain differential and integral cross sections. The cross sections obtained with the GP effect included were in much better agreement with the experimental results [19][20][21][22] than those obtained with the GP effect excluded. Hence, the GP effect is an important factor in accurate quantum scattering calculations done on the ground adiabatic electronic PES.…”
Section: Introductionsupporting
confidence: 75%
“…Kuppermann and co-workers 23 have performed scattering calculations that indicate that the GP can significantly affect the differential cross section in the DϩH 2 reaction at energies significantly below the conical intersection with the upper surface. Zare and co-workers 5,24 have measured the DCS and integral cross section ͑ICS͒ experimentally. Kuppermann and Wu 25 have found that the DCS was in better agreement with calculations including the GP than those without the GP.…”
Section: Introductionmentioning
confidence: 99%
“…Keogh et al calculated state-to-state integral cross sections for the exchange transition D + H 2 (1,1H>H + HD(lj) at translational energies of 23.5 kcal mol -1 and 18.9 kcal mol" 1 , using both quantum and quasiclassical calculations, and noted agreement with the experiments of Kliner, Adelman, and Zare [54] when taking into account the difficulties associated with using DBr as a source of D atoms [53]. Some of these cross sections are given in Table 5.1.…”
Section: Comparison Of State-to-state Exchange Cross Sections To Priomentioning
confidence: 60%
“…When the first accurate QM results came out [48,49,50], it was noted, with some consternation, that they were further from the experimental values than were the results of very approximate methods [51,52]. QCT and accurate QM rate coefficients were in general close to each other, but for vibrationally excited molecules, and even for some low rotational states in the D + H 2 (v = 0) exchange reaction [53], they differed considerably from the most recent and refined experiments [49,54,55,56,57,58]. Later, approximate QM methods would produce results in good agreement with accurate QM [59], furthering the controversy.…”
Section: Calculations On the Lsth And Dmbe Potential Energy Surfacesmentioning
confidence: 96%